Preparation of Well-Defined Double-Metal Cyanide Catalysts for Propylene Oxide Polymerization and CO2 Copolymerization - Seo, Yeong Hyun; Lee, Mi Ryu; Lee, Da Young; Park, Jun Hyeong; Seo, Hyeon Jeong; Park, Sang Uk; Kim, Hyunjin; Kim, Seung Joo; Lee, Bun Yeoul (Inorganic Chemistry, 2024)
Reevaluating the composition of the double metal cyanide catalyst (DMC) as a salt of (NC)6Co3- anions with 1:1 Zn2+/(X)Zn+ cations (X = Cl, RO, AcO), we prepared a series of well-defined DMCs, [ClZn+][Zn2+][(NC)6Co3-][ROH], [(RO)Zn+][Zn2+][(NC)6Co3-], [(AcO)Zn+][Zn2+][(NC)6Co3-], [(RO)Zn+]p[ClZn+](1-p)[Zn2+][(NC)6Co3-], [(AcO)Zn+]p[(tBuO)Zn+]q[Zn2+][(NC)6Co3-], and [(AcO)Zn+]p[(tBuO)Zn+]q[ClZn+]r[Zn2+][(NC)6Co3-]. The structure of [(MeOC3H6O)Zn+][Zn2+][(NC)6Co3-] was precisely determined at the atomic level through Rietveld refinement of the synchrotron X-ray powder diffraction data. By evaluating the catalyst’s performance in both propylene oxide (PO) polymerization and PO/CO2 copolymerization, a correlation between structure and performance was established on various aspects including activity, dispersity, unsaturation level, and carbonate fraction in the resulting polyols. Ultimately, our study identified highly efficient catalysts that outperformed the state-of-the-art benchmark DMC not only in PO polymerization [DMC-(OAc/OtBu/Cl)(0.59/0.38/0.15)] but also in PO/CO2 copolymerization [DMC-(OAc/OtBu)(0.95/0.08)].
Keywords: Atomic levels; Copolymerisation; Diffraction data; Double metal cyanide catalysts; Performance; Propylene oxide; Synchrotron X ray powder diffraction; Zn 2+; Zn cations; ]+ catalyst